Downton Abbey. Season 5 [videorecording (DVD)] - Bonneville, Hugh; Carmichael, Laura, 1986-; Carter, Jim, 1948-; Coyle, Brendan; Cullen, Tom, 1985-; Dockery, Michelle, 1981-; Doyle, Kevin, 1961-; Froggatt, Joanne, 1980-; James, Lily, 1989-; James-Collier, Rob; Leech, Allen; Logan, Phyllis; et al. (PBS Distribution, 2015)
As Season Five begins in 1924, the radio is the latest miracle, a new Labour government heralds changes through the land, and Downton's traditional ways are besieged on all fronts. Robert, Mary, and Branson must navigate these shifting sands together to ensure the future of the estate for generations to come. As Branson finds himself playing a more crucial role at Downton than ever before, he can't help but question his place in the world. Mary is finally coming to accept that she would like to marry again, but will she ever be able to find the same happiness that she had with Matthew? And with no news of her beloved Gregson, Edith suffers under the burden of her terrible secret. Downstairs, all of the servants must consider what effect social changes may have on their working lives. No one, Mr. Carson to Daisy, will be left unaffected. The Crawley family and the servants who work for them remain inseparably intertwined as they rise to meet the new challenges of the day.